Optimum Design of Shell and Tube Heat Exchanger Using Artificial Immune System Approach - Kumar, K.Vetrivel; Saravanan, M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This paper presents the economic optimization of shell and tube heat exchangers design approach through an artificial immune system algorithm for minimizing the cost. Since complex geometric parameters, with thermodynamic and fluid dynamic factors, consume more time and offer a minimum possibility for an optimum result in the case of conventional design, the design process becomes difficult. The proposed algorithm provides the designer with an optimum solution in less amount of time by analyzing three different case studies.Â  Three design variables such as shell internal diameter, tube outer diameter and baffle spacing from the different design parameters are taken into account for this optimization. The results are weighed against those obtained by various researchers.